2003
DOI: 10.1074/jbc.m209266200
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mRNAs Arising from Trans-splicing Code for Mitochondrial and Cytosolic Variants of Echinococcus granulosus Thioredoxin Glutathione Reductase

Abstract: Thioredoxin and glutathione systems are the major thiol-dependent redox systems in animal cells. They transfer via the reversible oxidoreduction of thiols the reducing equivalents of NADPH to numerous substrates and substrate reductases and constitute major defenses against oxidative stress. In this study, we cloned from the helminth parasite Echinococcus granulosus two trans-spliced mRNA variants that encode thioredoxin glutathione reductases (TGR). These variants code for mitochondrial and cytosolic selenocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 46 publications
6
53
0
Order By: Relevance
“…Indeed, a growing number of mitochondrial proteins are being found in both the cytosol and the mitochondrion (48,49). These include the histidyl-tRNA synthase (50), fumarase (51,52), copper-zinc superoxide dismutase (53), and dihydroxybutanone phosphate synthase (54) from yeast, thioredoxin from Drosophila (55), the thioredoxin glutathione reductase from Echinococcus (56), and several human proteins (48) including aspartate aminotransferase (57) and the Wilson's copper transport protein (58). Close examination of several of these proteins has revealed a multiplicity of mechanisms for the localization of proteins to the mitochondrion and the cytosol (48).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a growing number of mitochondrial proteins are being found in both the cytosol and the mitochondrion (48,49). These include the histidyl-tRNA synthase (50), fumarase (51,52), copper-zinc superoxide dismutase (53), and dihydroxybutanone phosphate synthase (54) from yeast, thioredoxin from Drosophila (55), the thioredoxin glutathione reductase from Echinococcus (56), and several human proteins (48) including aspartate aminotransferase (57) and the Wilson's copper transport protein (58). Close examination of several of these proteins has revealed a multiplicity of mechanisms for the localization of proteins to the mitochondrion and the cytosol (48).…”
Section: Discussionmentioning
confidence: 99%
“…In all cases mRNA from trizoled E. granulosus protoscoleces (larval worms) was used as a template for reverse transcription and PCR, using ThermoScript reverse transcriptase (Invitrogen) and Pfu (Fermentas), respectively. Forward and reverse gene-specific primers were derived from the previously published TGR sequence (5). In the case of mutant TGRs, the reverse primers were modified appropriately.…”
Section: Cloning Expression and Purification Of Recombinant Tgr Andmentioning
confidence: 99%
“…Instead, they rely exclusively on linked thioredoxin-glutathione systems, with TGR being the key enzyme that provides reducing equivalents to both pathways. Another feature of the linked systems in platyhelminths is that cytosolic and mitochondrial TGR derive from a single gene and have identical sequence, once the leader peptide of the mitochondrial variant is removed (5). In the mammalian hosts, different thioredoxin reductase isozymes function in the cytosol and the mitochondria (11,12), TGR expression is largely restricted to testis (13), and GR exists as a distinct gene (14).…”
mentioning
confidence: 99%
“…In addition, molecular characterization of the corresponding gene could also provide clues regarding the mechanism of generation of isoforms. Indeed, the analysis of TGR in E. granulosus revealed two trans-spliced cDNAs derived from a single gene [22]. These variants code for mitochondrial (mt) and cytosolic (c) TGRs, containing identical Grx and TrxR domains, but differing in their N-termini.…”
Section: S a L I N A S Lobanov And Gladyshev I N S E L E N I U M (20mentioning
confidence: 99%
“…The biochemical characterization of E. granulosus and T. crassiceps TGR indicated that the native enzyme shuttles electrons from NADPH to oxidized Trx (TR activity), GSSG (GR activity) and glutathione-mixed disulfi des (Grx activity). The stoichiometric inhibitory effect of auranofi n on both GR and TR activities of TGR indicates that the Sec-containing C-terminal redox center participates in electron transfer to GSSG and oxidized Trx [20,22]. In addition, TR and Grx domains can function either in coupled reactions or independently.…”
Section: S a L I N A S Lobanov And Gladyshev I N S E L E N I U M (20mentioning
confidence: 99%